(untitled) (Вісник: Міжнародні відносини, 2024)
The work is devoted to the history of Ukrainian-Azerbaijani relations. The article deals with issues of political, economic and cultural cooperation. The article also touches on the problems of the current state of bilateral relations. The position of Azerbaijan in the Ukrainian-Russian war, as well as the prospects of military cooperation between the two states, are considered. It turns out that today there are several "points of reference" in Ukrainian-Azerbaijani relations - military-technical cooperation, supply and transit of energy resources, conflicts with the Russian Federation, as well as the position on Crimea, relations within the framework of GUAM and the Eastern Partnership. The development of Ukrainian-Azerbaijani economic relations is of great importance, which is caused primarily by the special geopolitical situation of both countries. The article outlines the projected directions of further cooperation in the near and long term.